Bodies in Transition: Ethics in Xenotransplantation Research - Jasanoff, Sheila (The Hastings Center report, 2018)
Xenotransplantation, or the grafting of organs from one species to another, may seem at first a far cry from brain death, but there is rising hope in some quarters of the biomedical community that such transplants may reduce, even obviate, the need to harvest human organs—and hence eliminate the primary reason for needing an unambiguous definition of brain death. As with all research on the frontiers of biomedicine, xenotransplantation raises its own ethical quandaries. One concern that has long occupied ethical thought is the degree to which advances in science and technology should control the boundaries between the human and the nonhuman. Might the dimming of a previously entrenched bright line between species entail negative consequences for concepts, such as human dignity and bodily integrity, that historically anchored the protection of both human and animal subjects in biomedical treatment and research? To date, ethical thinking about xenotransplantation, and about gene editing, has largely been left in the hands of scientists, subject only to loose supervision by institutional review boards and animal welfare committees whose remit may be too narrow to address age-old moral concerns.